2009
DOI: 10.1038/ki.2009.245
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality and quality control of purified water and ultrapure dialysis fluids for online hemodiafiltration in routine clinical practice

Abstract: During online hemodiafiltration, patients are directly infused with sterile substitution solutions to maintain fluid balance. Adequate water treatment and a well-organized quality control process are essential to provide non-pyrogenic fluids with consistent optimal quality. We sought to assess water quality, the water treatment system, and the methods for surveillance of microbiological water quality in 10 Dutch dialysis centers that routinely treat patients with hemodiafiltration. Microbiological monitoring r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…We found 0.1 and 2.1% noncompliant UPW samples for bacterial count and endotoxin level when our reference limits were more stringent. We produced an ultrapure dialysate [28,29] achieving a 98.6% compliance rate (9 of 627 contaminated dialysate samples), a slightly lower rate than those reported in chronic dialysis facilities [27]. Our major concern was to guarantee a nonpyrogenic, ultrapure infusate, given that direct infusion of bacteria or endotoxin into the bloodstream through a contaminated infusate represents the worst-case scenario during on-line HDF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found 0.1 and 2.1% noncompliant UPW samples for bacterial count and endotoxin level when our reference limits were more stringent. We produced an ultrapure dialysate [28,29] achieving a 98.6% compliance rate (9 of 627 contaminated dialysate samples), a slightly lower rate than those reported in chronic dialysis facilities [27]. Our major concern was to guarantee a nonpyrogenic, ultrapure infusate, given that direct infusion of bacteria or endotoxin into the bloodstream through a contaminated infusate represents the worst-case scenario during on-line HDF.…”
Section: Discussionmentioning
confidence: 99%
“…A survey conducted in over 3,000 dialysis centers found that 93.6 and 97.4% of dialysis fluid samples were compliant according to a reference level for bacterial cell counts <100 CFU/ml and endotoxin <0.05 EU/ml, respectively [14]. In 10 Dutch chronic dialysis centers using on-line HDF, an even better microbiological quality of UPW and dialysis fluids was achieved (0.9% UPW samples >100 CFU/ml, and 0.3% >0.25 EU/ml) with a 99% compliance rate [27]. We found 0.1 and 2.1% noncompliant UPW samples for bacterial count and endotoxin level when our reference limits were more stringent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, this feature of HD therapy is often neglected, especially in the developing countries. 3 …”
Section: Introductionmentioning
confidence: 99%
“…The CONTRAST group has shown that infusate of adequate quality can be produced over a prolonged period of time. Moreover, no pyrogenic reactions were reported in HDF patients [12]. Also, markers of inflammation did not differ between the HDF and HD group [1,6].…”
Section: Safetymentioning
confidence: 99%